The board of directors in South Africa: Its role in corporate strategic planning - J. Viljoen (South African Journal of Business Management, 1986)
There is a considerable degree of uncertainty regarding the precise role of the board of directors in corporate strategic planning. With reference to the South African Company Law and practice the objectives of this paper are (i) to isolate and categorize possible alternative relationships between top management and the board of directors in matters of corporate strategy; (ii) to identify the level at which the board should become involved in corporate strategy; (iii) to suggest which elements of strategy should be the legitimate concern of the board; (iv) to propose procedural guidelines which will facilitate optimal board involvement in corporate strategy. The author concludes that the board of directors, in terms of its mandate, should not only become involved in strategy evaluation but also in the formulation and implementation of strategic plans. This is particularly true within the context of the current socio-economic and political environment in South Africa. The implications of this conclusion for the composition of the board and for the conducting of board affairs are discussed.
Keywords: 650